2023
DOI: 10.1111/1467-9566.13624
|View full text |Cite
|
Sign up to set email alerts
|

The social diagnoses of digital addictions: Technophobic ambivalences, the limits of the natural and imperatives of self‐governance in the information age

Abstract: The contemporary visibility of ‘digital addictions’ to online gaming, watching pornography, social media and so on suggests the discovery of some new form of technologically facilitated disease. Yet, what we actually see in the symptoms of these various behaviours when described as ‘addictions’ are a series of social problems that range from the interpersonal to the sociocultural. In the current article, I work to step outside of the individualising tendency of an addiction taxonomy to instead view digital add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The sexual content is obtained through certain software or websites, which aim to display sexual actors to increase the user's sexual desire [3]. There are various forms of cybersex behavior which include accessing pornography on the internet through sexual images, videos, erotic stories, films, and online games [4]. Therefore, it can be concluded that cybersex behavior refers to all activities related to pornography such as viewing or engaging in sexual activities with a partner, which are carried out in the virtual world.…”
Section: Introductionmentioning
confidence: 99%
“…The sexual content is obtained through certain software or websites, which aim to display sexual actors to increase the user's sexual desire [3]. There are various forms of cybersex behavior which include accessing pornography on the internet through sexual images, videos, erotic stories, films, and online games [4]. Therefore, it can be concluded that cybersex behavior refers to all activities related to pornography such as viewing or engaging in sexual activities with a partner, which are carried out in the virtual world.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study from New Zealand challenges this assumption, arguing that what we actually see in the symptoms of these various behaviours when described as 'addictions' are a series of social problems that range from the interpersonal to the sociocultural. 4 It specifically argues that a social diagnosis of the digital addiction concept tells us a great deal about contemporary cultural anxiety towards the ubiquity of digital media in our social worlds as it rubs up against concerns for productivity, socially lauded ideas of 'natural' behaviours, and worries about self-governance and self-control. This was a thought-provoking read, especially for those interested in debates about overdiagnosis.…”
mentioning
confidence: 99%